Higher Education under a Labour Government - Shattock, Michael (International Higher Education, 2008)
The Labour Party's victory in the general election of 1997 was greeted with a wave of popular enthusiasm. The new governments involvement includes the commitment to widening access to higher education, strengthening the system, while it also increased interventions. While there are danger signs in unwise ministerial interventionism, as a consequence of its size, its cost, and its economic importance higher education has become a legitimate object of public policy in a way that was barely conceivable two decades ago.